Pauline partnership in Christ Christian community and commitment in light of Roman law - Sampley, J. Paul (Philadelphia, PA Fortress, 1980)
Includes bibliographical references and index.
Keywords: Church -- biblical teaching; Christian life -- biblical teaching; Bible. N.T. Epistles of Paul -- theology